2016
DOI: 10.1097/hcr.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Electrical Stimulation on Physiologic and Functional Measurements in Patients With Heart Failure

Abstract: Neuromuscular electrical stimulation improved peak (Equation is included in full-text article.)O2, 6MWT distance, quality of life, muscle strength, endothelial function, and depressive symptoms in patients with HF and could be considered for inclusion in cardiac rehabilitation for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In this regard, the use of neuromuscular electrostimulation (NMES), which is usually used in chronic diseases with secondary sarcopenia, looks promising. [ 4 , 5 ] It has been shown that the use of NMES is not only safe in patients immediately after cardiovascular surgery, [ 6 , 7 ] but also reduces skeletal muscle proteolysis and weakness. [ 8 ] In patients with early activation after cardiovascular surgery, the use of NMES did not lead to additional improvement in muscle strength, which could be due to uncontrolled physical activity in the control.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the use of neuromuscular electrostimulation (NMES), which is usually used in chronic diseases with secondary sarcopenia, looks promising. [ 4 , 5 ] It has been shown that the use of NMES is not only safe in patients immediately after cardiovascular surgery, [ 6 , 7 ] but also reduces skeletal muscle proteolysis and weakness. [ 8 ] In patients with early activation after cardiovascular surgery, the use of NMES did not lead to additional improvement in muscle strength, which could be due to uncontrolled physical activity in the control.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty two [ 12 33 ] MAs reported on change in exercise capacity. Meta-analysis of VO 2peak was performed in 21 publications[ 12 16 , 18 33 ], 6MWD was analysed in 12 publications[ 12 17 , 19 , 20 , 22 , 25 , 28 , 33 ] peak power in two[ 12 , 21 ] and exercise time in one[ 26 ] publication. Analyses examined a range of exercise modalities across heart failure phenotypes, and Review Manager (Revman) was the most popular software package utilised.…”
Section: Resultsmentioning
confidence: 99%
“…Overall eleven [ 12 , 17 , 22 , 23 , 25 – 27 , 29 , 31 33 ] MAs failed to report anywhere within the publication any clear approach to deal with missing change SDs. Further examination of the 11 MAs revealed a range of methods were utilised in these analyses, including actual and approximate algebraic recalculations using actual or default p-values, post-intervention SDs and imputed SDs using correlation values ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary for AHF patients to achieve and maintain optimal physical function, and exercise therapy is required to maintain physical function in HF patients, especially in frail elderly subjects . EMS is a novel intervention that shows beneficial effects on both physical function and exercise capacity . Therefore, we postulated that EMS therapy would be effective in frail elderly AHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great deal of interest in use of electrical muscle stimulation (EMS), which can safely induce muscle contraction without the volitional effort of the patient, as a new training method that does not evoke dyspnea . Previous reports have indicated that lower‐limb EMS therapy can improve muscle strength, exercise capacity, and health‐related QOL and reduce HF‐related hospitalization in chronic HF patients, including elderly patients . More recently, randomized controlled trials (RCTs) have indicated that a short‐term lower‐limb EMS improved muscle strength, exercise capacity, and health‐related QOL in hospitalized HF patients, including few elderly patients .…”
Section: Introductionmentioning
confidence: 99%